(untitled) (Revista Nacional de Odontología, 2018)
Introduction: Disclosing the main clinical characteristics of some human papilloma viruses implications in the oral cavity allows health professionals to identify risk factors, as well as the main lesions asso- ciated with the virus, with the objective of providing timely treatment and thus avoid overlooking this type of injury. Characteristics: Human papillomavirus (hpv) belongs to the family of Papillomaviridae, it measures between 50 and 55 nm in diameter. It consists of small, untwisted, epitheliotropic dna viruses; its genome consists of double-stranded cdna. This virus can remain latent in the body for years without showing histological or clinical changes. It may also form benign papillomas or warts, these lesions consist of hyperplastic tissue, thickening of the epithelium’s spinous layer, and an increase in capillary proliferation. Results: Since the virus is exclusively epitheliotropic, its contagion occurs through microrruptures of the epithelium that expose basal surface cells to the virus, which explains the high frequency with which it presents in populations. Conclusions: General dentists should know the basic facts of hpv, so that when they identify any injury related to some of the hpv subtypes, they may guide the patient and offer an appropriate treatment when required.